1974
DOI: 10.1177/000992287401300817
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Review : Acute Renal Failure in Children: Principles of Management

Abstract: Acute renal failure is a complicated disturbance, which taxes the clinical skills of the physician. This paper reviews the metabolic derangements, the principles of treatment, the consequences, and the advances recently made in our understanding of the pathophysiology and management of acute renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Sixty-five per cent (47 of 72 cases) were associated with pneumonia and/or empyema (1)(2)(3)(4)(5)(6)10,11,(15)(16)(17)(18)(19)(26)(27)(28)31), and 31% were associated with meningitis (3,6,7,11,16,20,23,25,29,31). Sepsis was documented in 22% (1,2,18,(21)(22)(23)(24)(28)(29)(30)32) and otitis media in 7% of cases (3,19); one case was associated with mastoiditis (3). One study suggested that HUS typically followed pneumonia by approximately one week (18); however, our patients demonstrated both concurrently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty-five per cent (47 of 72 cases) were associated with pneumonia and/or empyema (1)(2)(3)(4)(5)(6)10,11,(15)(16)(17)(18)(19)(26)(27)(28)31), and 31% were associated with meningitis (3,6,7,11,16,20,23,25,29,31). Sepsis was documented in 22% (1,2,18,(21)(22)(23)(24)(28)(29)(30)32) and otitis media in 7% of cases (3,19); one case was associated with mastoiditis (3). One study suggested that HUS typically followed pneumonia by approximately one week (18); however, our patients demonstrated both concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that HUS typically followed pneumonia by approximately one week (18); however, our patients demonstrated both concurrently. Among the described cases, S pneumoniae was isolated from several different sites, including blood (61%) (2)(3)(4)(5)(6)11,16,18,(20)(21)(22)24,25,(27)(28)(29)(30)32), cerebrospinal fluid (27% ) (3,7,11,16,20,25,29) and pleural fluid (13%) (10,16,19,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation